Safety of shrimp peptide concentrate as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) (EFSA Journal, 2018)
Abstract Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on shrimp peptide concentrate as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is a peptide mixture obtained by an enzymatic proteolysis from northern shrimp (Pandalus borealis) shells and heads. The information provided on the composition, specifications, batch‐to‐batch variability, stability and production process of the NF is sufficient and does not raise safety concerns. The intention of the applicant is to use this NF as an ingredient in food supplements and to market it to adult consumers at a maximum proposed level of intake of 1,200 mg/day (corresponding to 17 mg/kg body weight (bw) per day for a 70 kg person). There are no concerns with regard to genotoxicity. The available human data do not raise safety concerns. Considering the no observed adverse effect level (NOAEL) of 2,000 mg/kg bw per day from a 90‐day repeated‐dose oral toxicity study, the maximum proposed level of intake and the nature of the NF, the Panel concludes that the margin of exposure (of 117) is sufficient. The Panel concludes that the NF, shrimp peptide concentrate, is safe to be used as a food supplement at the proposed maximum dose of 1,200 mg/day. The target population is adults. The Panel considered that the conclusion on the safety of the NF could not have been reached without the data from the unpublished study report on repeated‐dose 90‐day oral toxicity and from the unpublished study reports on two human studies.